Implementasi Kurikulum Merdeka Melalui Pembelajaran P5 (Projek Penguatan Profil Pelajar Pancasila) Dengan Tema Suara Demokrasi Pada Kelas XII SMK Bhakti Nusantara 666 - Diana, Aan; Mirochina, Chaerly; Badrudin, Badrudin (Peneliti.net, 2024)
The Merdeka Curriculum is a curriculum that provides flexibility to education units to develop learning according to the needs and characteristics of their students. One form of learning that can be developed in the Merdeka Curriculum is project-based learning (P5). P5 is learner-centered learning and focuses on developing the Pancasila learner profile. This study aims to examine the implementation of the Merdeka Curriculum through P5 learning with the theme of democratic voice in class XII of SMK Bhakti Nusantara 666. This research uses a qualitative approach with a case study method. The results showed that the implementation of the Merdeka Curriculum through P5 learning with the theme of democratic voices at SMK Bhakti Nusantara 666 went well. Learners can develop the profile of Pancasila students, especially the profile of Pancasila students as democratic citizens. Learners can understand the meaning of democracy and can practice democracy in everyday life. The implementation of Merdeka Curriculum through P5 learning with the theme of democratic voice with student council chair election activities can be an alternative to develop the profile of Pancasila learners in SMK. P5 learning can provide opportunities for students to develop critical thinking skills, problem solving skills, and communication skills.